Adherence to systemic therapy in patients with psoriasis during the COVID-19 pandemic: A multicenter study - Topal, İlteriş Oğuz; Kara Polat, Asude; Zindancı, İlkin; Altunay, İlknur Kıvanç; Özkök Akbulut, Tuğba; Arıkan, Eylem Emel; Topaloğlu Demir, Filiz; Sivaz, Onur; Karadağ, Ayşe Esra (Wiley, 2022)
Background: Adherence to treatment is important in chronic dermatological diseases. There are limited data regarding the adherence to treatment in patients with psoriasis during the COVID-19 pandemic. Aims: We aimed to determine the rates of adherence to systemic treatments in patients with psoriasis and to identify the causes of non-adherence during the COVID-19 pandemic. Methods: We conducted a cross-sectional multicenter study from May 2021 to August 2021. A questionnaire including items regarding sociodemographic characteristics of the patients, disease-related characteristics, and treatment-related characteristics were filled out by the physicians. The Psoriasis Area Severity Index (PASI), Hospital Anxiety, and Depression Scale, and the Dermatology Life Quality Index were calculated. The rate of adherence and non-adherence to treatment and reasons for non-adherence to treatment were examined. Results: A total of 342 patients with psoriasis were included (182 male/160 female) in the study. The mean age of the patients was 45.9 ± 14.2 years. The average duration of psoriasis was 192 ± 134.7 months. While the rate of adherence to treatment was 57.6%, the rate of non-adherence to treatment was 42.4%. There were no significant differences with respect to adherence to treatment in comparison with oral and injection-therapy groups. The most frequent reasons for non-adherence to treatment were inability to go to the hospital (19.2%), concern about the COVID-19 infection (16.3%), discontinuation of the treatment by the doctor (13.7%), inability to reach the doctor (7.3%), and inability to have access to the medication (7.3%). Conclusion: Adherence to oral and injection therapies was fairly high among our patients with psoriasis during the COVID-19 pandemic. Psoriasis severity and duration of medication use had a negative impact on adherence to treatment.
Keywords: Adherence; Psoriasis; COVID-19